Zimbabwe : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2020)
As part of a five-year project of the Enhanced Data Dissemination Initiative (EDDI) 2 Government Finance Statistics (GFS) Module on improving GFS and public-sector debt statistics in selected African countries, a mission was conducted in Harare, Zimbabwe during April 15-26, 2019. This mission was a follow up on a 2018 GFS technical assistance (TA) mission under the EDDI 2. The mission's objective was to review progress made and assisting with outstanding statistical issues that are important for sound policymaking in Zimbabwe. Some of the key outstanding issues raised by the IMF African Department prior to the mission were, the classification of government subsidies to state owned enterprises (SOEs); the identification of extrabudgetary units (EBUs) and classification of their operations; and the correct classification of other government transactions in line with a Government Finance Statistics Manual (GFSM) 2014 framework.